Using the Creative Thinking Skills in Teaching Arabic Language for Sixth Basic Grade pupils in the District of Nablus and their Impact on achievement and Solving Language Problems - Dhirar Kamel Mustafa Ishtayeh (My University, 2002)
This study aimed at using the creative thinking skills in teaching the Arabic Language for sixth basic grade pupils in the District of Nab Ius and their impact on achievement and solving language problems. The study problem was determined in the following two questions: 1. What is the impact of using the creative thinking skills in teaching the Arabic Language for sixth basic grade pupils in the District of Nablus and their impact on their achievement? 2. What is the impact of using the creative thinking skills in teaching the Arabic Language for sixth basic grade pupils in the District of Nablus and their impact on solving language problems? The study was carried out on a sample of sixth basic grade pupils at the government was schools in the District of Nablus during the first semester of the scholastic year 2001 -2002 . The size of the sample was (608) male and female pupils distributed at (16 ) schools divided into an experimental group and a controlling group each of them consisted of (8) schools. To answer the questions of the study and to verify its hypotheses this study depended on certain research procedures. The researcher prepared four tests that included the creative thinking skills: fluency, flexibility, originality, and elaboration. He also developed a testing instrument that consisted of a 38 - item questionnaire that included situations to develop the pupils abilities to solve problems. The validity of the two instruments was verified by a group of jury. The reliability of each of them was found out by using the Pearson correlation for the first instrument (the test) whose reliability correlation was (0.8665) and the Coder Richardson formula for the second instrument (the questionnaire) whose correlation was ( 0.8729 ). In this study the researcher depended on the experimental method by using arithmetic means, MANOV A and the Schefee test in order to find out whether there were significant differences. He also used the Hotling (t2) test, and the(t)- test of the correlated samples to find out the extent of retention between the immediate and deferred application of the test. The study reached the following findings: 1. There were significant differences at (α = 0.05 ) between the means of sixth basic grade pupils achievement due to the teaching method,sex achievement mean and the interaction between them. 2. There were no significant differences 'at (α = 0.05 ) between the means of sixth basic grade pupils achievement due to the interaction between the teaching method and sex. 3. There were significant differences at (α = 0.05 ) between the means of sixth basic grade pupils achievement due to the double interaction between the teaching method and the achievement level , and between the sex and the achievement mean , and due to the triple interaction between the teaching method, sex and achievement level. 4. There were significant differences at (α = 0.05 ) between the sixth basic grade pupils abilities in the Arabic language unit entitled "Science is the Way of Development", to solve Arabic language problems, due to the teaching method, sex and achievement level. 5. There were no significant differences at (α = 0.05 ) between the sixth basic grade pupils abilities in the Arabic language unit "Science is the Way of Development", to solve Arabic language problems due to the bi-interactions and the trio-interaction. 6. _ There were significant differences at (α = 0.05 ) between the sixth basic grade pupils abilities in the Arabic language unit "Science is the Way of Development" ,due to the dependent variables ( the first test and the second test) . In the light of the previous findings that this study reached, the researcher recommended the followings: - The new Palestinian curricula should give special attention to the students creative thinking at the various study levels and specializations including creative class participation, research, activities, teaching methods, evaluation methods and creative results. - Study subjects should include solving of real problems. - Training students and teachers during study and in-service for various strategies including problem-solving strategies. Teachers training courses should include subjects dedicated to creative thinking and development methods to provide them with adequate study and convince them of its importance so that these subjects could help them to develop the pupils' creative thinking. The researcher recommended conducting a similar field study about various class levels by taking other variables such as the impact of pupils socio- economic status, the parents' residence and culture to determine their reaction with each other. The researcher also recommended conducting studies about the impact of creative thinking in the method of solving problems in various subjects and class levels.

هدفت هذه الدراسة إلى استخدام مهارات التفكير الابداعي في تدريس اللغة العربية لتلاميذ الصف السادس بمحافظة نابلس وأثره في تحصيلهم وقدرتهم على حل المشكلات اللغوية، إذ تحددت مشكلة الدراسة في السؤالين الآتيين: 1. ما أثر استخدام مهارات التفكير الإبداعي في تدريس اللغة العربية لتلاميذ الصف السادس الأساسي بمحافظة نابلس على التحصيل الدراسي؟ 2. ما أثر استخدام مهارات التفكير الابداعي في تدريس اللغة العربية لتلاميذ الصف السادس الأساسي بمحافظة نابلس على حل المشكلات اللغوية؟ 3. هل توجد فروق ذات دلالة إحصائية عند مستوى الدلالة (α= 0.05) بين متوسطات تحصيل تلاميذ الصف السادس الاساسي وحدة "العلم سبيل الرقي" من مادة اللغة العربية تعزى للتفاعل بين المتغيرين التابعين (الاختبار الآني، والاختبار المؤجل)؟ وأجريت الدراسة على عينة من تلاميذ الصف السادس الاساسي في المدارس الحكومية بمحافظة نابلس، خلال الفصل الدراسي الاول من العام الدراسي (2001- 2002م)، بلغ حجمها ستمائة وثمانية طلاب، أي ما نسبته (25.5%)، موزعين على ست عشرة مدرسة، ثماني مدارس تجريبية والأخرى ضابطة. وللإجابة عن أسئلة الدراسة والتحقق من فرضياتها، اعتمدت هذه الدراسة التجريبية على اجراءات بحثية معينة، ومثلت في قيام الباحث بإعداد أربعة اختبارات ضمنت مهارات التفكير الابداعي الأربع، وهي: الطلاقة، والمرونة، والاصالة، والتوسع، وأداة قياس عبارة عن استبانة ضمنت مواقف لتطوير قدرات التلاميذ على حل المشكلات، وبعدد من الفقرات بلغ ثمان وثلاثين فقرة. وتم التأكد من صدق الأداتين بعرضهما على مجموعة من المحكمين، وحساب ثبات كل منهما باستخدام معامل ارتباط بيرسون للأداة الاولى (اختبار التحصيل) وكان معامل الثبات (0.8665)، واستخدمت معادلة كودر ريتشاردسون لاستخراج ثبات الاداة الثانية (الاستبانة) وكان معامل الثبات (0.8729). واستخدم الباحث في دراسته الحالية المنهج التجريبي، والمعالجات الاحصائية الآتية: المتوسطات الحسابية، وتحليل التباين الثلاثي، واختبار شيفيه للتأكد من وجود فروق ذات دلالة إحصائية، واختبار هوتلنج (ت2)، واختبار (ت) t- test للعينات المرتبطة، لمعرفة مدى الاحتفاظ بين التطبيق الآني والمؤجل للاختبار. وقد توصلت الدراسة الحالية إلى عدد من النتائج أهمها: 1. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) بين متوسطات تحصيل تلاميذ الصف السادس الاساسي، تعزى لكل من: طريقة التدريس، والجنس، والمعدل الدراسي، والتفاعل الثنائي بين طريقة التدريس والجنس والمعدل الدراسي. 2. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) بين متوسطات تحصيل تلاميذ الصف السادس الأساسي، تعزى للتفاعلات الثنائية بين طريقة التدريس والجنس والمعدل الدراسي. 3. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) بين قدرات - تلاميذ الصف السادس الأساسي، في وحدة "العلم سبيل الرقي" من مادة اللغة العربية على حل المشكلات اللغوية، تعزى لكل من: طريقة التدريس، والجنس، والمعدل الدراسي، والتفعيل الثنائي بين طريقة التدريس والمعدل الدراسي. 4. عدم وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α = 0.05) بين قدرات - تلاميذ الصف السادس الأساسي، في وحدة "العلم سبيل الرقي" من مادة اللغة العربية على حل المشكلات اللغوية، تعزى للتفاعلات الثنائية والتفاعل الثلاثي. 5. وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α=0.05) بين متوسطات تحصيل تلاميذ الصف السادس الأساسي في وحدة "العلم سبيل الرقي" من مادة اللغة العربية، تعزى للتفاعل بين المتغيرين التابعين (الاختبار الأول، الاختبار الثاني). وفي ضوء نتائج الدراسة، قدم الباحث بعض التوصيات مثل ضرورة أن تولي المناهج الفلسطينية الجديدة اهتماما خاصا بالتفكير الإبداعي لدى الطلبة في مختلف المستويات التعليمية والتخصصات الدراسية، وضرورة أن تتضمن الدورات التدريبية للمعلمين مساقات متخصصة على التفكير الإبداعي ووسائل تنميته حتى تتوافر لديهم استخدامه والقناعة بأهميته، بحيث تساعدهم هذه الدروس على تنمية التفكير الإبداعي لدى الطلبة. وأوصى الباحث بإجراء دراسة ميدانية تتناول مستويات صفية متعددة، وبأخذ متغيرات أخرى مثل أثر المستوى الاقتصادي الاجتماعي للتلاميذ، ومكان الإقامة، وثقافة الوالدين، ومستويات صفية مختلفة،.. الخ.
استخدام مهارات التفكير الإبداعي في تدريس مادة اللغة العربية لتلاميذ الصف السادس بمحافظة نابلس وأثره في تحصيلهم ومقدرتهم على حل المشكلات اللغوية